PEMBUATAN PAPAN MADING SEBAGAI SARANA INFORMASI LAYANAN BIMBINGAN DAN KONSELING DI SMP NEGERI MUARA TAMI KOTA JAYAPURA - Yansen Alberth Reba; Irmawati Irmawati; Luluk Faristha Putri (LP4MK STKIP PGRI Lubuklinggau, 2022)
The present Field Work Lecture activity aimed to: 1) provide an information service medium in the form of a bulletin board at school, 2) help students receive regular information services, 3) help students develop themselves and their ability to make decisions through the provision of concrete information services, and 4) facilitate Guidance and Counseling teachers to provide interesting and innovative information services. This activity applied the observation method and carried out work and evaluation programs. This field work lecture activity involved 10 students in the 5th semester and 2 supervisors from the Guidance and Counseling Program, Teaching and Education Faculty, Cendrawasih University. The activity was carried out for 1 week in the SMP Negeri Muara Tami Kota Jayapura, Papua environment. The research findings were obtained from all accumulated questions/statements in which students answered 'strongly agree' as much as 32%, students answered 'agree' as much as 18%, students answered 'quite agree' as much as 8%, students answered 'disagree' as much as 14% , and students answered 'strongly disagree' as much as 28%. Thus, it was concluded that 58% of students of SMP Negeri Muara Tami received and felt helped by providing information services through the provision of bulletin boards.